Determination of alpha-napthyl acetate esterase activity of native and frozen-thawed bull sperm acrosome - Ülkü Nur Canbolat; İlhami Çelik; Rukiye Erdoğan (Eurasian Journal of Veterinary Sciences)
Aim: The assay of the leakage of acrosomal enzymes into seminal plasma might provide an early and sensitive evidence for membrane damage ocurred during freezing of semen for artificial insemination. Alpha-naphthyl acetate esterase is one of the acrosomal enzymes that can be used for this purpose. In the the present study, the positivity rates and localization pattern of alphanaphthyl acetate esterase in the spermatozoa of both native and frozen-thawed bull semen samples were determined by light microscopy. Materials and Methods: Semen samples of 7 bull were used as material. Smears were prepared from native and frozen-thawed semen samples. The enzyme was demonstrated by a cytochemical method. Specimens were observed under ligth microscope. Positivity rates of alpha-naphtyl acetate eseterasepositive spermatozoa, distribution and localization pattern of the enzymatic reaction were determined. Results: The reddish-brown enzymatic reaction was peculiar to spermatozoon acrosome. In some cells, the enzymatic reaction was observed as a narrow band located on acrosomal membrane. The enzymatic reaction intesity was not similar in all cells and was weaker in some cells. The reaction product primarily located in the acrosome. There were large individual differences in alpha-naphthyl acetate esterase positivity rates of the native sperm samples. The native semen samples with low spermatozoon vitality and motility tended to display lower of alpha-naphthyl acetate esterase positivity rates. Freeze- thawing process significantly decreased alpha-naphthyl acetate esterase positivity rates of the samples. Conclusion: Acrosomal alpha-naphtyl acetate esterase might be considered as a significant parameter in the asssessment of availibility for freezing and to determine fertility potential of the bull semen.